Response of high-altitude clouds to the galactic cosmic ray cycles in tropical regions - Miyahara, Hiroko; Kusano, Kanya; Kataoka, Ryuho; Shima, Shin‐ichiro; Touber, Emile (Frontiers in Earth Science, 2023)
Galactic cosmic rays are one of the possible mediators of the solar influence on climate. However, the impacts of GCR on clouds and climate systems are not fully understood. In this paper, we show that the high-altitude clouds associated with deep convective activities are responding to the decadal-scale cycles of GCRs and that the susceptible areas are seasonally variable. Most notable responses were found in August over tropical land areas, suggesting that the susceptivity of clouds to GCRs depends on the depth of convective activities and the abundance of aerosol precursor materials. Furthermore, following the activation of high-altitude cloud formation, an increase in sea surface temperature (SST) gradient was observed over the Pacific. Although the response of sea surface temperature to solar activity has mostly been discussed as mediated by solar radiations, we propose that another mechanism is possible: through the impact of GCRs on clouds and the resultant changes in atmospheric circulations.